2002
DOI: 10.1161/01.cir.0000037520.89770.5e
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural Statin Medication Reduces the Extent of Periprocedural Non–Q-Wave Myocardial Infarction

Abstract: Background-Stenting-related myocardial injury has been recognized as a frequent and prognostically important event, the extent of which depends on microcirculatory impairment in association with platelet aggregation, inflammation, and increased oxidative stress. Recent studies underscored the non-lipid-lowering effects of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins) with antithrombotic, antiinflammatory, and antioxidative aspects. Thus, we tested the hypothesis that preprocedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(73 citation statements)
references
References 25 publications
1
68
0
4
Order By: Relevance
“…9 We expected an incidence of postprocedural CK-MB elevation of Ϸ30% in the placebo group and 10% in the treatment group. Thus, a sample size of 120 patients (with 60 in each group) would provide 80% power to detect a difference with an alpha (probability value) of 0.05.…”
Section: Discussionmentioning
confidence: 94%
“…9 We expected an incidence of postprocedural CK-MB elevation of Ϸ30% in the placebo group and 10% in the treatment group. Thus, a sample size of 120 patients (with 60 in each group) would provide 80% power to detect a difference with an alpha (probability value) of 0.05.…”
Section: Discussionmentioning
confidence: 94%
“…[23][24][25] Many studies have demonstrated that early statin therapy among PCI patients is associated with significant advantages for decreased mortality and morbidity in different patient subsets. 10,[26][27][28] Although the mechanism is not entirely clear, the anti-inflammatory effects of statins might contribute to the reduced myocardial injury during PCI. In the present study, prior statin therapy had no significant effect on postprocedural troponin elevation.…”
Section: Discussionmentioning
confidence: 99%
“…44 In patients undergoing stenting of a de novo stenosis, the incidence of periprocedural myocardial injury, as assessed by analysis of creatine kinase and troponin T, was reduced by preprocedural treatment with HMG-CoA reductase inhibitors. 45 This beneficial effect is most likely attributable to antiinflammatory properties of HMG-CoA reductase inhibitors. 46 Thus, patients at risk of coronary microembolization may indeed benefit from acute antiinflammatory treatment with glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%